Cyclic Voltammetric Investigations of Thiazine Dyes on Modified Electrodes. (12th February 2013) - Chakraborty, Amitabha; Ahamed, Shamsuzzaman; Pal, Subrata; Saha, Swapan K.
Abstract : Electrochemical behavior of five progressively alkylated thiazine dyes has been investigated at glassy carbon/montmorillonite and glassy carbon/zeolite electrodes. Quantitative characteristics, associated with the positions of peak potentials (E a and E c ) and current ratios (i a / i c ), are measured with scan rates. The peak current observed in the modified electrodes is dependent on both the porosity and nature and number of sites involved in partitioning the complex into film. The values of diffusion coefficient for different dyes have been calculated from electrochemical data. It is suggested that in clay-modified electrode along with physical diffusion the process of electron hopping seems to be most likely.